Factors Affecting Tourist Decisions to Travel to the Suci Keramat Water Tourism Park in Sugian Village, Lombok Timur Regency - Rahmad Difa Mardiansyah; Akhmad Jufri; Endang Astuti (Tinta Emas Publisher, 2024)
In recent years, Indonesia's tourism landscape, particularly in regions like East Lombok Regency, has undergone a profound transformation. There's a growing emphasis on sustainable tourism practices, reflecting a recognition of the need to balance economic development with environmental preservation and social inclusivity. This study delves into the factors shaping tourists' decisions to visit the Holy Sacred Water Tourism Park in Sugian Village, East Lombok Regency, with a focus on sustainable tourism development principles. Employing a quantitative research approach, the study investigates the causal relationships between dependent variables (tourist decision-making) and independent variables (infrastructure facilities, services, tourist attractions, tourism costs, and tourist attractions distance). Surveys via questionnaires were administered to visitors of the Sugian Village Holy Sacred Water Tourism Park from May 2023 to March 2024, utilizing non-random sampling with an accidental sampling technique. Primary data collected through questionnaires was complemented by secondary data from various sources, including destination managers, local government authorities, and economic literature. Multiple linear regression analysis was conducted to assess the relationships between variables, with classical assumption tests ensuring the analysis's validity. The findings underscored the significant influence of infrastructure facilities, services, tourist attractions, tourism costs, and tourist attractions distance on tourists' decision-making processes. It's recommended that tourism managers prioritize maintaining affordable costs and enhancing infrastructure, services, and attractions to improve visitor satisfaction and boost visitation to the Sacred Sacred Water Tourism Park in Sugian Village. This proactive approach is vital for sustaining and nurturing tourism growth in the region, aligning with sustainable development goals.